Pengaruh firm size, debt to assets ratio, dan working capital turnover terhadap return on assets dengan current ratio sebagai variabel moderasi - Almira, Meila; Damayanti, Santi (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
This research aims to explain the influence of Firm Size, Debt to Assets Ratio and Working Capital Turn Over on Return On Assets with the Current Ratio as a Moderating Variable. This type of research is research with a quantitative approach. The data used is secondary data obtained from www.idx.co.id. The research population consisted of 34 Mining Sector Companies listed on the Indonesia Stock Exchange for the 2014-2021 period with a sample size of 6 Companies using purposive sampling, data collection was carried out through documentation and library research. Data testing in this research used the classic assumption test, Pearson Product Moment correlation coefficient test, coefficient of determination test and partial or simultaneous hypothesis testing, multiple linear regression analysis and moderated regression analysis with data processing using the IBM SPSS 25.0 program. Research findings show that Firm Size, debt to assets ratio, and working capital turnover have a significant effect on the Current Ratio and Return On Assets in retail associations on the IDX. Simultaneously, these three variables explain most of the variation in Current Ratio and Return On Assets. In addition, Current Ratio plays a role as a moderating variable, explaining fifty four persent of the variation in the joint influence of these three variables on Return On Assets.